The role of muscle damage in the etiology of overtraining syndrome - Kaasik, P.; Seene, T. (LASE Journal of Sport Science, 2013)
A complex of conditions leads to the development of overtraining syndrome. Overtraining syndrome is associated with peripheral-cellular and central-cerebral processes, hormonal-neural regulation and transmission mechanisms. The decrease in physical work capacity is substantially related to the muscle damage and a decrease in muscle oxidative potential. The review describe mainly the balance between training stimulus and recovery, skeletal muscle damage and defense systems, regeneration as well as the role of reactive oxygen species, heat shock proteins and insulin-like growth factors in overtrained skeletal muscles.